Overview of Composite Metal Foams and Their Properties and Performance. Issue 11 (13th March 2017) - Marx, Jacob; Rabiei, Afsaneh
Abstract : This paper reviews the background and evolution of composite metal foam (CMF) from its inception until now. A broad understanding of the processing and basic mechanical, microstructural, and physical properties of different types of composite metal foams is discussed in the first part of the paper. In the second part, some recent studies on high strain rate properties, ballistic performance, radiation attenuation, and thermal properties of composite metal foams are discussed and compared with other bulk and control materials. These properties suggest many potential applications for this novel material in a broad range of engineering structures from ballistic armors to trains', cars', buses', helicopters' crashworthiness systems, and many others such as nuclear casks and thermal insulating units. Abstract : Composite Metal Foam (CMF) has shown about two order of magnitude higher energy absorption than comparable bulk materials while maintaining a third of their density. High‐impact resistance, ballistic and blast energy absorption capabilities highlight some of the unique properties of CMF. Nuclear radiation shielding and thermal insulation are other areas in which composite metal foam excels and outperforms bulk metals. The image shows two types of composite metal foams before and after compression loading without any bulging or shear.